MEK inhibition causes BIM stabilization and increased sensitivity to BCL-2 family member inhibitors in RAS-MAPK-mutated neuroblastoma - Eleveld, Thomas F.; Vernooij, Lindy; Schild, Linda; Koopmans, Bianca; Alles, Lindy K.; Ebus, Marli E.; Dandis, Rana; van Tinteren, Harm; Caron, Huib N.; Koster, Jan; van Noesel, Max M.; Tytgat, Godelieve A. M.; et al. (Frontiers in Oncology, 2023)
Introduction: Mutations affecting the RAS-MAPK pathway occur frequently in relapsed neuroblastoma tumors and are associated with response to MEK inhibition in vitro. However, these inhibitors alone do not lead to tumor regression in vivo, indicating the need for combination therapy. Methods and results: Via high-throughput combination screening, we identified that the MEK inhibitor trametinib can be combined with BCL-2 family member inhibitors, to efficiently inhibit growth of neuroblastoma cell lines with RAS-MAPK mutations. Suppressing the RAS-MAPK pathway with trametinib led to an increase in pro-apoptotic BIM, resulting in more BIM binding to anti-apoptotic BCL-2 family members. By favoring the formation of these complexes, trametinib treatment enhances sensitivity to compounds targeting anti-apoptotic BCL-2 family members. In vitro validation studies confirmed that this sensitizing effect is dependent on an active RAS-MAPK pathway. In vivo combination of trametinib with BCL-2 inhibitors led to tumor inhibition in NRAS-mutant and NF1-deleted xenografts. Conclusion: Together, these results show that combining MEK inhibition with BCL-2 family member inhibition could potentially improve therapeutic outcomes for RAS-MAPK-mutated neuroblastoma patients.